Better understanding of mechanisms of schizophrenia and bipolar disorder: from human gene expression profiles to mouse models - Lin, Chi-Ying (2011)
The molecular mechanisms of major mental illnesses, such as schizophrenia and bipolar disorder, are unclear. To address this fundamental question, many groups have studied molecular expression profiles in postmortem brains and other tissues from patients compared with those from normal controls. Development of unbiased high-throughput approaches, such as microarray, RNA-seq, and proteomics, have supported and facilitated this endeavor. In addition to genes directly involved in neuron/glia signaling, especially those encoding for synaptic proteins, genes for metabolic cascades are differentially expressed in the brains of patients with schizophrenia and bipolar disorder, compared with those from normal controls in DNA microarray studies. Here we propose the importance and usefulness of genetic mouse models in which such differentially expressed molecules are modulated. These animal models allow us to dissect the mechanisms of how such molecular changes in patient brains may play a role in neuronal circuitries and overall behavioral phenotypes. We also point out that models in which the metabolic genes are modified are obviously untested from mental illness viewpoints, suggesting the potential to re-address these models with behavioral assays and neurochemical assessments.